Proteinaceous secretion of bioadhesive produced during crawling and settlement of Crassostrea gigas larvae. Issue 1 (December 2018) - Foulon, Valentin; Artigaud, Sébastien; Buscaglia, Manon; Bernay, Benoit; Fabioux, Caroline; Petton, Bruno; Elies, Philippe; Boukerma, Kada; Hellio, Claire; Guérard, Fabienne; Boudry, Pierre
Abstract Bioadhesion of marine organisms has been intensively studied over the last decade because of their ability to attach in various wet environmental conditions and the potential this offers for biotechnology applications. Many marine mollusc species are characterized by a two-phase life history: pelagic larvae settle prior to metamorphosis to a benthic stage. The oysterCrassostrea gigas has been extensively studied for its economic and ecological importance. However, the bioadhesive produced by ready to settle larvae of this species has been little studied. The pediveliger stage of oysters is characterized by the genesis of a specific organ essential for adhesion, the foot. Our scanning electron microscopy and histology analysis revealed that inC. gigas the adhesive is produced by several foot glands. This adhesive is composed of numerous fibres of differing structure, suggesting differences in chemical composition and function. Fourier transformed infrared spectroscopy indicated a mainly proteinaceous composition. Proteomic analysis of footprints was able to identify 42 proteins, among which, one uncharacterized protein was selected on the basis of its pediveliger transcriptome specificity and then located by mRNAin situ hybridization, revealing its potential role during substrate exploration before oyster larva settlement.